A Comparative Study Investigating the Impact of Group Singing on Social-Emotional Competencies and Academic Burnout in College Students - Jiang, Xin (SAGE open, 2025)
Participation in group music activities can promote the development of social-emotional competencies (SEC) while decreasing burnout. This study aimed to assess the influence of group singing activities on Chinese college students’ SEC and academic burnout. A cross-sectional comparative research design was employed to investigate the characteristics of social-emotional development of competencies and academic burnout among college students in eastern China who engaged in group singing activities and those who did not. Data were collected using the Social and Emotional Competence Assessment Battery for Adults (SECAB-A) and the Maslach Burnout Inventory-Student Survey (MBI-SS) from 364 individuals who participated in group singing and 360 who did not. The independent samples t-test, Pearson correlation and regression analysis analyses revealed that revealed significant statistical disparities in all evaluated variables between the two groups of participants. Engaging in collective singing endeavors can significantly enhance the cultivation of SEC among college students and mitigate the occurrence of academic burnout. Furthermore, the findings validated an inverse association between SEC enhancement and academic burnout and highlighted their predictive relationship.